(untitled) (Research, Society and Development, 2022)
Buffel grass has characteristics of resistance and rapid recovery to prolonged drought, however, few studies indicate this resistance to salinity. Thus, the objective was to evaluate the relationship between salt stress and the growth dynamics, green mass production and area of Buffel grass. The experiment was conducted in an entirely randomized design, with three levels of salinity and ten repetitions, totaling 30 experimental units. Measurements of height, cutting and weighing of green mass were made in three periods, with intervals of 28 days between them, and photography of the leaves for analysis in ImageJ software in the last period. The data obtained were submitted to the Shapiro-Wilk normality test and Bartlett’s homogeneity test. Kruskal-Wallis non-parametric test and Dunn’s post-test was applied for data that did not follow normality, and ANOVA test and Tukey’s post-test for those that followed normality and homogeneity. The results indicate that there was no significant difference in height for the treatments with or without salt, so even with the addition of salt there was no interference in growth, but when compared in relation to the periods, it can be observed that the last period was different from the others, this can be explained by the vegetative vigor of the plant, because when it is younger it has more efficient cell multiplication, but as it suffers injuries, the vigor is decreased and growth is slower. Therefore, there are some differences in the behavior of grass submitted to salinity, but they do not significantly interfere in its development.